Rosyjskojęzyczny patriotyzm ukraiński. O zmianie funkcji języka rosyjskiego na Ukrainie pod wpływem Euromajdanu i wojny w Donbasie - Studenna-Skrukwa, Marta (Kultura i Społeczeństwo, 2015)
This article analyzes the phenomenon of Ukrainian Russian-language patriotism. In the first part, the author concentrates on the socio-linguistic situation in Ukraine since 1991. The next part contains a brief description of language policy in Ukraine in the 1990s and at the beginning of the 21st century, and presents the attitude of contemporary Ukrainian society to the Russian language. The main part of the text presents the changes in perception of the Russian language that have occurred in Ukraine as a consequence of the anti-regime protests at the end of 2013 and beginning of 2014 and then Russia’s violation of the country’s territorial integrity. The author predicts that the Russian language will not only continue to be widely represented in the Ukrainian public sphere, but will also form part of Ukraine’s cultural heritage. At the same time, she suggests that it is likely that the Russian language in Ukraine will become an object for expressions of resentment, contempt, or even hatred toward Russia.